PENGARUH METODE PEMBELAJARAN EKSPERIMEN TERHADAP PENINGKATAN HASIL BELAJAR SISWA (Studi Eksperimen di Kelas VII SMP pada Konsep Energi dalam Sistem Kehidupan) - Dina Rahmawati; Adi Maladona; Aden Arif Gaffar (BIO EDUCATIO : (The Journal of Science and Biology Education), 2018)
Abstract This research purposed to know the influences of student learning result in 7th grade The First Public Junior High School  Ciamis on the Energy in Living Systems concept. The research was conducted  from 29 November 2013 to 1 March 2014. The population in this study were all classes in 7th grade The First Public Junior High School Ciamis which consists of 9 classes as much as 337 student. The samples used in this research were 2 classes taken using cluster random sampling technique, which VII D and VII E. Instrument that used in this study is achievement test on the Energy in Living Systems concept, form multiple choice with four option as much as 50 question. Data analysis techniques used by t test. The result researching at the  experiment class pointed that pre test = 8,87 and post test = 22,19, where was at the control class pre test = 9,47 and post test = 10,84. The median score was determined is 22,5, as for the real of  median scores= 25 and control class="10", research result show that in class experimental has exceeded the value of Minimum Completness Chriterian (MCC) and control class didn’t sure pass it yet. Seen from  N-gain eskperimen =0,70 including the high category and  N-gain kontrol = 0,23 including the low category. Thus, experimental learning methods affect the improvement of student learning result in the experimental class than questioning teaching methods in the control class and appropriate used for the process of learning the concept of Energy in Life Systems on 7th grade The First Public Junior High School Ciamis. Keyword : Learning result, Experiment Method